Paradoxes of the Relationship between Literature and Visuality in Zygmunt Haupt’s Prose Writings - Niewiadomski, Andrzej ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
Visual arts are the natural interpretative context of the prose work of Zygmunt Haupt, the author who, apart from writing, dealt with painting, drawing and graphics. The mechanisms of painting vision can easily be captured in his stories, but it is worth remembering that he understood plastic art very broadly, including not only painting and sculpture, but also architecture, photography, cinema and theater. Haupt uses these areas of art as a tool to support writing efforts that allow: 1/ to capture the inexpressible, 2/ indicate the complexity of the modern world, 3/ signal the trauma of past experiences. In Haupt’s prose, visual art is also a search for the truth of things and events, emerging from the clash of the possibilities of various conventions and artistic strategies.